2020
DOI: 10.1021/acs.langmuir.9b03293
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine α-CoOOH Nanorods Activated with Iron for Exceptional Oxygen Evolution Reaction

Abstract: Two-dimensional oxyhydroxide materials are proved to be a potential candidate for oxygen evolution reaction (OER). Robust, efficient, and cost-effective electrocatalysts are critical to overcome the sluggish kinetics and high overpotential of OERs. Herein, a simple co-precipitation method followed by solvothermal treatment is used to synthesize Fe-doped α-CoOOH at higher pH under optimum conditions for OER. The α-Fe 0.24 Co 0.76 OOH/NF illustrates superior OER electrocatalytic performance and requires an overp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…The difference in binding energy of the deconvoluted peaks of the Co 2p XPS spectra is ∼ 16 eV which indicates the presence of Co 3+ . However if Co 2+ is present in the system the difference in binding energy between the 2p 3/2 and 2p 1/2 energy state is closer to ∼15 eV [48] . This is further validated by the appearance of a broad peak at 784.3 eV and 801.0 eV originating from satellite peaks.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…The difference in binding energy of the deconvoluted peaks of the Co 2p XPS spectra is ∼ 16 eV which indicates the presence of Co 3+ . However if Co 2+ is present in the system the difference in binding energy between the 2p 3/2 and 2p 1/2 energy state is closer to ∼15 eV [48] . This is further validated by the appearance of a broad peak at 784.3 eV and 801.0 eV originating from satellite peaks.…”
Section: Resultsmentioning
confidence: 74%
“…The ratio of Co 2+ /Co 3+ determined from the ratio of the area under the corresponding peaks are found to be ∼0.64 (Table S1). Interestingly, upon Fe incorporation, it is observed that the peaks shifted to a slightly higher binding energy (Figure S6b) [48,49] . Also, the ratio of Co 2+ /Co 3+ decreased to ∼0.37 which indicates the facile oxidation of Co 2+ to Co 3+ in presence of Fe.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Among the leading OER catalysts, transition-metal-based oxyhydroxides and layered double hydroxides (LDHs) have gained considerable attention due to their excellent catalytic activity and abundant availability in the earth’s crust. It is known that incorporation of Fe (III) in oxyhydroxides has outperformed the OER kinetics, although the key factor in improvement is still under consideration. , Besides Fe (III), cobalt is introduced into nickel hydroxides to boost the OER kinetics in water oxidation via constructing NiCo-LDHs. , However, the performance was not as good as that of NiFe-LDHs. Meanwhile, the substitution of Fe in cobalt hydroxides is well documented. , Likewise, before employing LDHs as electrode materials, improved conductivity and the specific surface area need considerable attention to advance OER kinetics. , The size of the hydroxides reported so far is too large to improve the OER kinetics intensely due to the limited accessibility of edges and corner sites . Typically, metal hydroxide nanosheets with dimensions less than 200 nm are being synthesized by microemulsion, plasma etching, layer growth inhibitors, and solvent exfoliations …”
Section: Introductionmentioning
confidence: 99%